Community structure of woody plants of Roraima savannahs, Brazil - Miranda, Izildinha Souza; Absy, Maria Lúcia; Rebêlo, George Henrique (Plant Ecology, 2003)
Patterns of diversity and community organisation of woody species of savannahs in Roraima, northern Brazil, were investigated, to relate structural data with edaphic factors and to analyse floristic relationships using classification and ordination techniques. The species studied refer to an inventory of 45 plots of 150 x 10 m (0.15 ha) distributed in the Roraima savannahs. We identified 13,410 woody individuals, belonging to 30 families, 52 genera and 71 species. The percentage of rare species is high, 58%. The richness, diversity, density and basal area of the studied plots suggest that Roraima savannahs are poor in species. The most important species include element dwarf shrubs (Byrsonima verbascifolia, Tibouchina aspera and Cassia obtusifolia), shrubby (Psidium guianense, Randia formosa, Casearia sylvestris, Erythroxylum suberosum, Tocoyena formosa and Mimosa microcephala) and arboreal (Curatella americana, B. crassifolia, B. coccolobifolia, Bowdichia virgilioides, Roupala montana, Antonia ovata, Genipa americana, Vitex schomburgkiana, Peltogyne campestris, Xylopia aromatica and Himatanthus articulatus). Correlation between edaphic factors and vegetation indices reveal that density seems to be more sensitive to edaphic factors than to basal area and diversity. Density correlated significantly with levels of A1, K and the quantity of sand in the soil. Edaphic factors can explain the distribution and importance of some species, such as: B. virgilioides, R. montana and P. guianense. Classification analysis tended to confirm PCA results, separating Roraima savannahs into three large clusters. This suggests that ecological differentiation is based not only on species density but also on basal area. Ordination describes floristic variation but does not identify all edaphic gradients.
Keywords: Community Structure; Floristics; Ordination; Savanna; Soil Property; Species Diversity; Vegetation Classification; Woody Plant; Antonia Ovata; Bowdichia Virgilioides; Byrsonima Coccolobifolia; Byrsonima Crassifolia; Casearia; Casearia Sylvestris; Cassia; Curatella Americana; Erythroxylum; Genipa; Genipa Americana; Himatanthus; Microcephala; Mimosa; Peltogyne; Psidium; Psidium Guajava; Randia Formosa; Roupala; Roupala Montana; Senna; Senna Obtusifolia; Tibouchina; Tocoyena; Vitex; Xylopia